2018
DOI: 10.1161/circoutcomes.118.005040
|View full text |Cite
|
Sign up to set email alerts
|

Sex Disparities in Authorship Order of Cardiology Scientific Publications

Abstract: Background: Despite advances in the representation of women in medical training, women continue to be underrepresented in cardiology, academic medicine, and more specifically, in senior positions within academic medicine. Identifying disparities in research productivity and acknowledgment can highlight barriers to female representation in academic cardiology leadership, as well as in academic promotion. Methods and Results: This bibliomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 31 publications
2
32
1
5
Order By: Relevance
“…Esta investigación tampoco halló una tendencia en el tiempo para la primera autoría o corresponsalía femenina (21) . Estos hallazgos no son consistentes con el incremento global de la participación femenina en las publicaciones académicas (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) . Sin embargo, en algunos estudios se ha encontrado una desaceleración del incremento o incluso un efecto meseta al alcanzar cierta proporción de primeras autoras o autoras corresponsales (10,11,13,14) .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Esta investigación tampoco halló una tendencia en el tiempo para la primera autoría o corresponsalía femenina (21) . Estos hallazgos no son consistentes con el incremento global de la participación femenina en las publicaciones académicas (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) . Sin embargo, en algunos estudios se ha encontrado una desaceleración del incremento o incluso un efecto meseta al alcanzar cierta proporción de primeras autoras o autoras corresponsales (10,11,13,14) .…”
Section: Discussionunclassified
“…Las distintas formas de participación femenina en la autoría fueron consideradas como: a) Primera autoría femenina, si el primer autor listado es una mujer; b) autoría senior femenina, si el último autor listado es una mujer (8,9,(11)(12)(13)16,17) ; c) autor corresponsal mujer, si el autor corresponsal -en el que se indique dirección o correo electrónicoes una mujer; d) existencia de al menos una mujer dentro de la lista de autores de la publicación; y e) proporción de autores mujeres (calculado dividiendo el número de autoras entre el número total de autores de la publicación). En las publicaciones con una única autora, se consideró que una mujer cumplía el rol de «primer autor», «autor senior» y «autor corresponsal» simultáneamente.…”
Section: Variablesunclassified
See 1 more Smart Citation
“…The possibility of systematic bias in peer review of grant applications is of great concern to both applicants and funding agencies [1][2][3][4][5][6][7]. Disparities in success rates of scientific publishing [8][9][10] and in obtaining grant awards [11][12][13] raise questions of whether reviewer bias based on applicant demographics (race, gender, age, career stage, etc.) or institutional reputation unfairly influence the review outcomes which shape funding and publication decisions [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that the female representation in published cardiology research has increased over the past 4 decades, but women continue to be underrepresented when considering the total number of female researchers. 7 The study analyzing citations from 2379 articles from the top 20 impact cardiology journals from the Entrez database on PubMed, in 2017, has reported that less than one third of the publications of single authors had a female authorship. Of the publications with multiple authors, only 15% of the corresponding authors were women.…”
mentioning
confidence: 99%